Influence of Weed Management Practices on Weeds, Yield and Economics of Fingermillet (Eleusine coracana L. Gaertn) - Kujur, S.; Singh, V. K.; Gupta, D. K.; Tandon, A.; Ekka, V.; Agrawal, H. P. (International Journal of Bio-resource and Stress Management, 2018)
A Field experiment was conducted at I.G.K.V., Rajmohini Devi College of Agricultural and Research Station, Ambikapur (C.G), during kharif 2015. The experiment was laid out in Randomized Complete Block Design (RCBD) with ten treatments, replicated thrice. Observations were taken on weed, plant growth and yield attributes, yield, and economic parameters. Panicum maxima, Elusine indica, Cyperus spp., Cynodon dactylon, Celosia argentea, Alternanthera sessilis, Alternenthera triandra, Ageratum conyzoides were found to be domimant weeds. All weed control treatments significantly reduced the weed density and dry weight of weed resulting significant increase in yield of fingermillet over weedy check. Among the weed management practices, significantly lowest density, dry matter of weeds, higher weed control efficiency and low weed index were recorded under hoeing twice by wheel hoe between rows and intra-row manual weeding followed by hand weeding twice. The maximum grain yield (32.58 and 29.23 q ha-1), straw yield (94.05 and 84.98 q ha-1), gross return (62973 and 56594 ` ha-1), net return (42024 and 32495 ` ha-1) and B:C ratio (2.01 and 1.35) were also recorded under hoeing twice by wheel hoe between rows and intra-row manual weeding followed by two hand weeding at 20 and 40 DAS. Among herbicidal treatment, application of isoproturon @ 0.5 pre emergence+2, 4-D Na salt @ 0.5 kg ha-1 post emergence appeared to be effective, economically viable for weed control, higher grain yield and net return.